Dynamic impact protective body armour: A comprehensive appraisal on panel engineering design and its prospective materials - Mulat Alubel Abtew; François Boussu; Pascal Bruniaux (Defence Technology, 2021)
Personal body armour is one of the most important pieces of equipment to protect human beings from various critical and fatal injuries. In today’s modern world, various organizations including law enforcement and security service have made it mandatory for their personnel to wear personal protection system while on field duty. However, the systems should comprise an improved ballistic performance, light-weighted, flexible as well as comfortable panel not only to be accepted with a wider range but also for effective performances of the consumer. Generally, the overall performances of the protective body armour could be affected by various parameters including armour design techniques, type of materials used and finishing of the panels. The current paper aims to critically review state-of-art for armour panel design techniques and the different perspective body armour materials. The paper starts by discussing the different body armour and its category. Later, the different states of technology for armour panel design (mostly for women), its problems and the possible solutions will be cited. Later, the commonly used different polymeric fibrous and the future possible advanced materials including carbon nanotube (CNT), Graphene CNT and shear thickening fluids (STFs) treated materials for developing the reinforced body armour panel will be discussed. The authors believe that this paper will enlighten useful guidelines and procedures about the different panel design techniques and current and promising future materials for researchers, designers, engineers and manufacturers working on the impact resistance body armour field.